Democratic governance with government scope, objectives, and significance - Argyriades, Demetrios; Moleketi, Geraldine Fraser (2009)
The mega-crisis that began in 2008 has been seen as presaging more than the meltdown of the financial markets. It has also been seen as marking the passage of a doctrine and ideology which swept across the world in the course of 30 years from the 1980s onwards. Briefly stated, in the words of the current President of the United States, this doctrine held that government was "the problem"; indeed "that every problem can be solved if only government could step out of the way; that if government were... dismantled...that would.. benefit us all" (Obama 2009a).

A new term with old roots was coined: "good governance." Dating from the 18th century, it served to give the impression that democracy was assured if government would "step away." However, in the measure that governments worldwide have been struggling to bail out ailing banks and enterprises, we have been reaping the fruits of this singular ideology. On the social and ecological fronts, the downsides of this doctrine have been monumentally costly, though all too often swept under the rug. Against the backdrop, the article explores the damage that disdain of government has inflicted on the public sector.
Keywords: Governance; Public administration -- Economic aspects; Public administration -- South Africa; Democracy -- Economic aspects